If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-18+2=-2(x+3)
We move all terms to the left:
-18+2-(-2(x+3))=0
We add all the numbers together, and all the variables
-(-2(x+3))-16=0
We calculate terms in parentheses: -(-2(x+3)), so:We get rid of parentheses
-2(x+3)
We multiply parentheses
-2x-6
Back to the equation:
-(-2x-6)
2x+6-16=0
We add all the numbers together, and all the variables
2x-10=0
We move all terms containing x to the left, all other terms to the right
2x=10
x=10/2
x=5
| -(v-70)=63 | | 211/12x3/4=x | | 450=(40*x)+(1.5*x) | | 456=-8(-8x-9) | | 42=-3x=54 | | 5x+14=x-1 | | 9+19=-4(7x-7) | | 190=10(-5x-6) | | -10(w-89)=-80 | | 190=10(-5x-6 | | y+6=18/2 | | 5(4x+9)=-24+49 | | -5+4u=-29 | | 3x-(7x+20)=6-(13x-3) | | 52-2(y-4)-yy=14 | | 2(4x+9)=-21+7 | | m+19/7=4 | | (w+3)-2w-(1-3w)=2 | | 4(v-3)-5=-3(-8v+9)-4v | | 2(w+7)-4w=20 | | -304=194+-3q | | -9=-11+(b)/(8) | | 3x+7=5x-11=52-2x | | -9c-18=-81 | | 12x-28=24 | | 5(2x+6)=-43+3 | | x4-56=98 | | 4(v-3)-5=-3(-8+9)-4v | | -34=4v+6(v-4) | | 5g+9=74 | | -6(1-6p)+6p=-174 | | 2y-12=66 |